Wet-mixed high-strength concrete and preparation process thereof
Through the coordinated use and modification of basalt fibers and PVA fibers, combined with hollow glass microbeads, the problem of the decline in mechanical properties of existing concrete after weight reduction is solved, lightweight, high-strength wet-mixed high-strength concrete is achieved, and the pressure resistance is improved , crack resistance and construction properties.
Patent Information
- Application Number
- CN202411413230.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-17
AI Technical Summary
While reducing weight, existing concrete is difficult to have high strength in both mechanical properties, and the way of adding modified materials affects its fluidity and dispersion, resulting in a degradation of performance.
The coordinated use of basalt fiber and PVA fiber is adopted, and through hydroxylation and modification treatment, combined with hollow glass microbeads, the proportion and process of concrete are optimized to form lightweight, high-strength wet mixing high-strength concrete.
It achieves a lightweight concrete with excellent strength, toughness and lightweight, improves compressive, flexural and impact resistance, enhances construction and durability, and improves flowability and dispersion.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and specifically discloses a wet-mixed high-strength concrete and a preparation process thereof. Background Art
[0002] Concrete is the main raw material for civil engineering projects. It is mainly made by mixing sand, gravel and cement. It has a simple production process, excellent product performance and wide application. With the continuous development of urbanization, the requirements for concrete used in building materials are getting higher and higher, requiring it to have the characteristics of light weight and high strength.
[0003] In the prior art, resin particles and hollow microspheres are often used to replace part of the sand and gravel to reduce the weight of concrete. However, the introduction of too much of them will lead to a decrease in mechanical properties, so it is necessary to improve the performance of concrete by adding other modified materials. The addition of these materials affects the fluidity of concrete, and their dispersion also has a great influence on the performance of concrete. If the addition method is improper, it will lead to a decrease in performance. In summary, it is of great significance to study a lightweight, high-strength and high-quality concrete and its preparation process. Summary of the invention
[0004] The object of the present invention is to provide a wet-mix high-strength concrete and a preparation process thereof, so as to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solution: A process for preparing wet-mixed high-strength concrete: comprising the following steps: S1: taking basalt fiber, performing hydroxylation treatment, and obtaining hydroxylated basalt fiber; taking hydroxylated basalt fiber, adding it into acetone and dispersing it evenly, adding glutaraldehyde, citrate B, and hydroxy silicone oil, stirring at 50-55° C. for 4-6 hours, filtering, washing, and drying, and obtaining modified basalt fiber; S2: Weigh cement, crushed stone and sand and mix them to obtain a dry mix; add a water reducing agent, deionized water, hollow glass microspheres, PVA fibers and modified basalt fibers to the dry mix in sequence and mix them evenly to obtain a wet mix high-strength concrete.
[0006] More optimally, the modified basalt fiber includes the following raw materials, calculated by weight: 10-15 parts of hydroxylated basalt fiber, 100-120 parts of acetone, 2-3 parts of glutaraldehyde, 2-3 parts of citrate B, and 4-6 parts of hydroxy silicone oil.
[0007] More optimally, the concrete includes the following raw materials, calculated by mass: 420-450 parts of cement, 1000-1150 parts of crushed stone, 500-600 parts of sand, 100-120 parts of hollow glass microspheres, 120-160 parts of water, 3-6 parts of water reducer, 10-25 parts of PVA fiber, and 20-40 parts of modified basalt fiber.
[0008] More optimally, the length of the PVA fiber is 18-25 mm; the length of the basalt fiber is 6-12 mm.
[0009] More optimally, the length of the PVA fiber is 20 mm; the length of the basalt fiber is 9 mm.
[0010] More optimally, the cement is 42.5 grade ordinary Portland cement; the sand is river sand with a particle size of ≤5mm; the crushed stone particle size is 5mm~31.5mm; and the water reducer is a polycarboxylic acid type water reducer.
[0011] More optimally, the PVA fiber is pre-modified to obtain modified PVA fiber, which is then introduced into wet-mixed high-strength concrete; the specific modification process is as follows: PVA fiber is dispersed in a solvent, the pH is adjusted to 3-4, hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, N-hydroxyethyl-2-pyrrolidone, and glutaraldehyde are added, the temperature is raised to 55-60°C and stirred for 4-6 hours, washed, and dried to obtain modified PVA fiber.
[0012] More optimally, the modified PVA fiber includes the following raw materials, calculated by weight: 10 to 15 parts of PVA fiber, 1 to 1.5 parts of hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, 0.5 to 1 parts of N-hydroxyethyl-2-pyrrolidone, and 3 to 5 parts of glutaraldehyde.
[0013] More optimally, the preparation of the hydroxylated basalt fiber includes the following steps: taking basalt fiber, adding it into Piranha solution, treating it at 90-95° C. for 1-2 hours, taking it out, washing it, and drying it to obtain hydroxylated basalt fiber.
[0014] More optimally, in the Piranha solution, V concentrated sulfuric acid: V hydrogen peroxide = (2-3): 1; the hydroxylated basalt fiber comprises the following raw materials, calculated by weight: 10-15 parts of basalt fiber and 60-80 parts of Piranha solution.
[0015] More optimally, in the Piranha solution, V concentrated sulfuric acid (98%, Nanjing reagent): V hydrogen peroxide = 3:1.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are: In the plan, cement, gravel and sand are used as the base materials, and hollow glass beads, PVA fibers and basalt fibers are introduced as additives; thus forming a lightweight, high-strength wet-mix high-strength concrete.
[0017] Among them, hollow glass microspheres can not only improve lightness, heat insulation, and sound insulation performance, but also improve fluidity. Due to the smooth surface, they can play a "ball effect", reduce friction inside the concrete, and enhance construction performance. However, if more of them are introduced, the density will decrease, resulting in reduced mechanical properties such as compression and flexural resistance. Therefore, in the plan, PVA fiber and basalt fiber are further introduced to complement each other and improve the strength of concrete.
[0018] Among them, PVA fiber and basalt fiber use fibers of different lengths and properties; a mixture of slightly longer 18~25mm soft fibers (PVA fibers) and short-cut hard fibers (basalt fibers) is used to connect the concrete network, effectively enhancing the density and improving the strength of concrete.
[0019] First, PVA fiber has good dispersibility and adhesion. When introduced into concrete, it can reduce the plastic shrinkage and drying shrinkage of concrete, thereby reducing the occurrence of cracks; its softness enhances the impact resistance of concrete. Basalt fiber is a hard fiber with high strength and modulus, and it has natural silicate compatibility, which can combine cement with sand and gravel, improve the mechanical properties of concrete such as compression and flexural resistance, and increase the durability of concrete. Compared with the introduction of single-nature fibers, the effective synergy of the two fibers enhances the strength of wet-mixed high-strength concrete and makes up for the shortcomings of hollow glass microspheres.
[0020] Secondly, in order to further improve the strength of concrete, PVA fiber and basalt fiber are further modified.
[0021] The present invention uses citrate B and hydroxy silicone oil to modify basalt fiber; citrate B has a plasticizing effect and can improve the fluidity of concrete; hydroxy silicone oil has good lubricity, reduces friction between aggregate and cement, and improves the fluidity of concrete; at the same time, silicone oil has a defoaming effect and can improve the surface quality of concrete.
[0022] The present invention uses hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer and N-hydroxyethyl-2-pyrrolidone to modify PVA fiber, and improve the dispersibility and adhesion of PVA fiber in concrete. Among them, hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer is grafted as a long chain segment, which can improve the dispersibility of the fiber in concrete. At the same time, the long chain has the advantages of good hydrophilicity and large molecular weight, and has a strong coating performance for dry mix, which can increase the two-link network, effectively transfer stress, and reduce crack expansion. The grafting of short-chain N-hydroxyethyl-2-pyrrolidone is beneficial to increase the surface activity of the fiber and the compatibility with the concrete matrix; increase the interaction between molecules, improve the adhesion between the fiber and the concrete matrix; can reduce the adverse effect of soil on the water reducer; and more effectively improve the mechanical properties and durability of the concrete.
[0023] In summary, the present invention controls the addition amount of hollow glass microspheres, PVA fibers, and basalt fibers to obtain lightweight concrete with excellent strength and toughness. The lengths of the PVA fibers and basalt fibers also need to be controlled to ensure that the dispersion and fluidity are not affected and to achieve the best reinforcement and toughening effect. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The following parts are by mass unless otherwise specified; Example 1: S1: 15 parts of 20 mm PVA fibers were dispersed in 90 parts of water, the pH was adjusted to 3, 1.5 parts of hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, 0.6 parts of N-hydroxyethyl-2-pyrrolidone, and 4 parts of glutaraldehyde were added, the temperature was raised to 60° C. and stirred for 5 h, washed, and dried to obtain modified PVA fibers; S2: Take 12 parts of 9 mm basalt fiber, add them into 70 parts of Piranha solution, treat at 90°C for 1.5 hours, take out, wash and dry to obtain hydroxylated basalt fiber; S3: Take 12 parts of hydroxylated basalt fiber, add 120 parts of acetone, disperse evenly, add 3 parts of glutaraldehyde, 2 parts of citrate B, 5 parts of hydroxy silicone oil, stir at 52°C for 5h, filter, wash and dry to obtain modified basalt fiber; S4: 450 parts of cement, 1150 parts of crushed stone and 500 parts of sand are mixed evenly to obtain a dry mix; 5 parts of a water reducing agent and 130 parts of water, 120 parts of hollow glass microspheres, 20 parts of modified PVA fibers and 35 parts of modified basalt fibers are added to the dry mix and mixed evenly to obtain a wet-mixed high-strength concrete.
[0026] Example 2: S1: 15 parts of 20 mm PVA fibers were dispersed in 90 parts of water, the pH was adjusted to 3, 1.5 parts of hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, 0.6 parts of N-hydroxyethyl-2-pyrrolidone, and 4 parts of glutaraldehyde were added, the temperature was raised to 60° C. and stirred for 5 h, washed, and dried to obtain modified PVA fibers; S2: Take 10 parts of 9 mm basalt fiber, add them into 60 parts of Piranha solution, treat at 90°C for 1.5 hours, take out, wash and dry to obtain hydroxylated basalt fiber; S3: Take 10 parts of hydroxylated basalt fiber, add 120 parts of acetone, disperse evenly, add 2 parts of glutaraldehyde, 2 parts of citrate B, 4 parts of hydroxy silicone oil, stir at 52°C for 5h, filter, wash and dry to obtain modified basalt fiber; S4: 420 parts of cement, 1000 parts of crushed stone and 600 parts of sand are mixed evenly to obtain a dry mix; 3 parts of a water reducing agent and 160 parts of water, 100 parts of hollow glass microspheres, 15 parts of modified PVA fibers and 40 parts of modified basalt fibers are added to the dry mix, and mixed evenly to obtain a wet-mixed high-strength concrete.
[0027] Example 3: S1: 15 parts of 20 mm PVA fibers were dispersed in 90 parts of water, the pH was adjusted to 3, 1.5 parts of hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, 0.6 parts of N-hydroxyethyl-2-pyrrolidone, and 4 parts of glutaraldehyde were added, the temperature was raised to 60° C. and stirred for 5 h, washed, and dried to obtain modified PVA fibers; S2: Take 15 parts of 9 mm basalt fiber, add them into 80 parts of Piranha solution, treat at 90°C for 1.5 hours, take out, wash and dry to obtain hydroxylated basalt fiber; S3: Take 15 parts of hydroxylated basalt fiber, add 120 parts of acetone, disperse evenly, add 3 parts of glutaraldehyde, 3 parts of citrate B, and 6 parts of hydroxy silicone oil, stir at 52°C for 5h, filter, wash, and dry to obtain modified basalt fiber; S4: 450 parts of cement, 1150 parts of crushed stone and 600 parts of sand are mixed evenly to obtain a dry mix; 6 parts of a water reducing agent and 120 parts of water, 100 parts of hollow glass microspheres, 22 parts of modified PVA fibers and 30 parts of modified basalt fibers are added to the dry mix and mixed evenly to obtain a wet-mixed high-strength concrete.
[0028] Example 4: S1: 15 parts of 18 mm PVA fibers were dispersed in 90 parts of water, the pH was adjusted to 3, 1.5 parts of hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, 0.6 parts of N-hydroxyethyl-2-pyrrolidone, and 4 parts of glutaraldehyde were added, the temperature was raised to 60° C. and stirred for 5 h, washed, and dried to obtain modified PVA fibers; S2: Take 12 parts of 12 mm basalt fiber, add them into 70 parts of Piranha solution, treat at 90°C for 1.5 hours, take out, wash and dry to obtain hydroxylated basalt fiber; S3: Take 12 parts of hydroxylated basalt fiber, add 120 parts of acetone, disperse evenly, add 3 parts of glutaraldehyde, 2 parts of citrate B, 5 parts of hydroxy silicone oil, stir at 52°C for 5h, filter, wash and dry to obtain modified basalt fiber; S4: 450 parts of cement, 1150 parts of crushed stone and 500 parts of sand are mixed evenly to obtain a dry mix; 5 parts of a water reducing agent and 130 parts of water, 120 parts of hollow glass microspheres, 20 parts of modified PVA fibers and 35 parts of modified basalt fibers are added to the dry mix and mixed evenly to obtain a wet-mixed high-strength concrete.
[0029] Example 5: S1: 15 parts of 25 mm PVA fibers were dispersed in 90 parts of water, the pH was adjusted to 3, 1.5 parts of hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, 0.6 parts of N-hydroxyethyl-2-pyrrolidone, and 4 parts of glutaraldehyde were added, the temperature was raised to 60° C. and stirred for 5 h, washed, and dried to obtain modified PVA fibers; S2: Take 12 parts of 6 mm basalt fiber, add them into 70 parts of Piranha solution, treat at 90°C for 1.5 hours, take out, wash and dry to obtain hydroxylated basalt fiber; S3: Take 12 parts of hydroxylated basalt fiber, add 120 parts of acetone, disperse evenly, add 3 parts of glutaraldehyde, 2 parts of citrate B, 5 parts of hydroxy silicone oil, stir at 52°C for 5h, filter, wash and dry to obtain modified basalt fiber; S4: 450 parts of cement, 1150 parts of crushed stone and 500 parts of sand are mixed evenly to obtain a dry mix; 5 parts of a water reducing agent and 130 parts of water, 120 parts of hollow glass microspheres, 20 parts of modified PVA fibers and 35 parts of modified basalt fibers are added to the dry mix and mixed evenly to obtain a wet-mixed high-strength concrete.
[0030] Example 6: S1: 15 parts of 25 mm PVA fibers were dispersed in 90 parts of water, the pH was adjusted to 3, 1.5 parts of hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, 0.6 parts of N-hydroxyethyl-2-pyrrolidone, and 4 parts of glutaraldehyde were added, the temperature was raised to 60° C. and stirred for 5 h, washed, and dried to obtain modified PVA fibers; S2: Take 12 parts of 12 mm basalt fiber, add them into 70 parts of Piranha solution, treat at 90°C for 1.5 hours, take out, wash and dry to obtain hydroxylated basalt fiber; S3: Take 12 parts of hydroxylated basalt fiber, add 120 parts of acetone, disperse evenly, add 3 parts of glutaraldehyde, 2 parts of citrate B, 5 parts of hydroxy silicone oil, stir at 52°C for 5h, filter, wash and dry to obtain modified basalt fiber; S4: 450 parts of cement, 1150 parts of crushed stone and 500 parts of sand are mixed evenly to obtain a dry mix; 5 parts of a water reducing agent and 130 parts of water, 120 parts of hollow glass microspheres, 20 parts of modified PVA fibers and 35 parts of modified basalt fibers are added to the dry mix and mixed evenly to obtain a wet-mixed high-strength concrete.
[0031] Example 7: S1: 15 parts of 18 mm PVA fibers were dispersed in 90 parts of water, the pH was adjusted to 3, 1.5 parts of hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, 0.6 parts of N-hydroxyethyl-2-pyrrolidone, and 4 parts of glutaraldehyde were added, the temperature was raised to 60° C. and stirred for 5 h, washed, and dried to obtain modified PVA fibers; S2: Take 12 parts of 6 mm basalt fiber, add them into 70 parts of Piranha solution, treat at 90°C for 1.5 hours, take out, wash and dry to obtain hydroxylated basalt fiber; S3: Take 12 parts of hydroxylated basalt fiber, add 120 parts of acetone, disperse evenly, add 3 parts of glutaraldehyde, 2 parts of citrate B, 5 parts of hydroxy silicone oil, stir at 52°C for 5h, filter, wash and dry to obtain modified basalt fiber; S4: 450 parts of cement, 1150 parts of crushed stone and 500 parts of sand are mixed evenly to obtain a dry mix; 5 parts of a water reducing agent and 130 parts of water, 120 parts of hollow glass microspheres, 20 parts of modified PVA fibers and 35 parts of modified basalt fibers are added to the dry mix and mixed evenly to obtain a wet-mixed high-strength concrete.
[0032] Comparative Example 1 (changing the amount of modified PVA fiber and modified basalt fiber added, and the other method steps are consistent with Example 1): S1: 15 parts of 20 mm PVA fiber are dispersed in 90 parts of water, the pH is adjusted to 3, 1.5 parts of hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, 0.6 parts of N-hydroxyethyl-2-pyrrolidone, and 4 parts of glutaraldehyde are added, the temperature is raised to 60° C. and stirred for 5 hours, washed, and dried to obtain modified PVA fiber; S2: Take 12 parts of 9 mm basalt fiber, add them into 70 parts of Piranha solution, treat at 90°C for 1.5 hours, take out, wash and dry to obtain hydroxylated basalt fiber; S3: Take 12 parts of hydroxylated basalt fiber, add 120 parts of acetone, disperse evenly, add 3 parts of glutaraldehyde, 2 parts of citrate B, 5 parts of hydroxy silicone oil, stir at 52°C for 5h, filter, wash and dry to obtain modified basalt fiber; S4: 450 parts of cement, 1150 parts of crushed stone and 500 parts of sand are mixed evenly to obtain a dry mix; 5 parts of a water reducing agent and 130 parts of water, 120 parts of hollow glass microspheres, 45 parts of modified PVA fibers and 10 parts of modified basalt fibers are added to the dry mix and mixed evenly to obtain a wet-mixed high-strength concrete.
[0033] Comparative Example 2 (the preparation method of modified PVA fiber and modified basalt fiber was changed, and the other method steps were consistent with Example 1): S1: 15 parts of 20 mm PVA fiber were dispersed in 90 parts of water, the pH was adjusted to 3, 3 parts of glutaraldehyde, 2 parts of citrate B, and 5 parts of hydroxy silicone oil were added, the temperature was raised to 60° C. and stirred for 5 h, washed, and dried to obtain modified PVA fiber; S2: Take 12 parts of 9 mm basalt fiber, add them into 70 parts of Piranha solution, treat at 90°C for 1.5 hours, take out, wash and dry to obtain hydroxylated basalt fiber; S3: Take 12 parts of hydroxylated basalt fiber, add 120 parts of water, disperse evenly, add 1.5 parts of hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, 0.6 parts of N-hydroxyethyl-2-pyrrolidone, 4 parts of glutaraldehyde, stir at 60°C for 5h, filter, wash and dry to obtain modified basalt fiber; S5: 450 parts of cement, 1150 parts of crushed stone and 500 parts of sand are mixed evenly to obtain a dry mix; 5 parts of a water reducing agent and 130 parts of water, 120 parts of hollow glass microspheres, 20 parts of PVA fibers and 35 parts of modified basalt fibers are added to the dry mix and mixed evenly to obtain a wet-mixed high-strength concrete.
[0034] Comparative Example 3 (changing the lengths of the PVA fiber and the basalt fiber, and the remaining steps are consistent with those of Example 1): S1: 15 parts of 6 mm PVA fiber are dispersed in 90 parts of water, the pH is adjusted to 3, 1.5 parts of hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, 0.6 parts of N-hydroxyethyl-2-pyrrolidone, and 4 parts of glutaraldehyde are added, the temperature is raised to 60° C. and stirred for 5 h, washed, and dried to obtain modified PVA fiber; S2: Take 12 parts of 20 mm basalt fiber, add them into 70 parts of Piranha solution, treat at 90°C for 1.5 hours, take out, wash and dry to obtain hydroxylated basalt fiber; S3: Take 12 parts of hydroxylated basalt fiber, add 120 parts of acetone, disperse evenly, add 3 parts of glutaraldehyde, 2 parts of citrate B, 5 parts of hydroxy silicone oil, stir at 52°C for 5h, filter, wash and dry to obtain modified basalt fiber; S4: 450 parts of cement, 1150 parts of crushed stone and 500 parts of sand are mixed evenly to obtain a dry mix; 5 parts of a water reducing agent and 130 parts of water, 120 parts of hollow glass microspheres, 20 parts of modified PVA fibers and 35 parts of modified basalt fibers are added to the dry mix and mixed evenly to obtain a wet-mixed high-strength concrete.
[0035] Comparative Example 4 (changing the preparation method of concrete, and the remaining method steps are consistent with Example 1): S1: 450 parts of cement, 1150 parts of crushed stone, and 500 parts of sand are mixed evenly to obtain a dry mix; 5 parts of water reducer, 130 parts of water, 3 parts of hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, 1 part of N-hydroxyethyl-2-pyrrolidone, 5 parts of citrate B, 14 parts of hydroxy silicone oil, 120 parts of hollow glass microspheres, 20 parts of 20 mm PVA fiber, and 35 parts of 9 mm basalt fiber are added to the dry mix, and mixed evenly to obtain concrete.
[0036] In the above examples, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: ethanol (CAS: 64-17-5); acetone (CAS: 67-64-1); hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer (EMT10, Xinxin Jiali); N-hydroxyethyl-2-pyrrolidone (CAS: 3445-11-2); glutaraldehyde (CAS: 111-30-8); zinc sulfate ( S22124, Shanghai Yuanye); sodium sulfate (S24155, Shanghai Yuanye); glyoxal (CAS: 107-22-2); polycarboxylic acid water reducer (polycarboxylic acid water reducer 40%, product number 0213, Hubei Shiteng Chemical Technology Co., Ltd.); basalt fiber (Shandong Oude Chemical Fiber Products Co., Ltd.); PVA fiber (Guangdong Zhongtian Port Bridge Construction Engineering Co., Ltd.); citrate B (B20912, Shanghai Yuanye); hydroxy silicone oil (IOTA2050, Anhui Iota Silicone Oil Co., Ltd.).
[0037] Experiment: Take a 150x150x150 (mm) mold, fix a HRB400 steel bar with a diameter of 12mm at the geometric center, pour the concrete prepared in Examples 1 to 7 and Comparative Examples 1 to 4 respectively, start the vibration table to vibrate, and use a spatula to insert and tamp along the inner wall for multiple times, the vibration time is 3 minutes, smooth the surface, demould, put it in a standard curing room for curing for 24 hours, and obtain a sample; use a WA-2000 electro-hydraulic servo universal testing machine to test the compressive strength and cracking load of the sample; see the table below for specific data;
[0038] Conclusion: In comparative example 1, the addition amount of PVA fiber and modified basalt fiber was changed, and the performance decreased, which shows the importance of raw material ratio; in comparative example 2, the preparation method of PVA fiber and modified basalt fiber was changed, and citrate B and hydroxy silicone oil originally used for modified basalt fiber were used for modified PVA fiber, and hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer and N-hydroxyethyl-2-pyrrolidone originally used for modified PVA fiber were used for modified basalt. Due to problems such as dispersibility, the performance was not as good as that in the embodiment, which shows that the modification step is of great significance; in comparative example 3, the length of PVA fiber and basalt fiber was changed, resulting in decreased performance; in comparative example 4, the preparation method of concrete was changed, and PVA fiber, basalt fiber, hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, N-hydroxyethyl-2-pyrrolidone, citrate B and hydroxy silicone oil were directly added, and the performance decreased significantly; in summary, the concrete prepared by the present invention has the characteristics of light weight and high strength, excellent mechanical properties and toughness, and good compressive strength and crack resistance.
[0039] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A process for preparing wet-mixed high-strength concrete, Features: The following steps are involved: S1: taking basalt fiber and subjecting it to hydroxylation treatment to obtain hydroxylated basalt fiber; Take hydroxylated basalt fiber, add it into acetone and disperse it evenly, add glutaraldehyde, citrate B and hydroxy silicone oil, stir at 50-55°C for 4-6h, filter, wash and dry to obtain modified basalt fiber; S2: Weigh cement, crushed stone and sand and mix them to obtain a dry mix; add a water reducing agent, deionized water, hollow glass microspheres, PVA fibers and modified basalt fibers to the dry mix in sequence and mix them evenly to obtain a wet mix high-strength concrete.
2. A process for preparing wet-mixed high-strength concrete according to claim 1, Features: The modified basalt fiber comprises the following raw materials, calculated by weight: 10-15 parts of hydroxylated basalt fiber, 100-120 parts of acetone, 2-3 parts of glutaraldehyde, 2-3 parts of citrate B, and 4-6 parts of hydroxy silicone oil.
3. A process for preparing wet-mixed high-strength concrete according to claim 1, Features: The concrete includes the following raw materials, calculated by weight: 420-450 parts of cement, 1000-1150 parts of crushed stone, 500-600 parts of sand, 100-120 parts of hollow glass microspheres, 120-160 parts of water, 3-6 parts of water reducing agent, 10-25 parts of PVA fiber, and 20-40 parts of modified basalt fiber.
4. A process for preparing wet-mixed high-strength concrete according to claim 1, Features: The length of the PVA fiber is 18-25 mm; the length of the basalt fiber is 6-12 mm.
5. A process for preparing wet-mixed high-strength concrete according to claim 1, Features: The cement is 42.5 grade ordinary Portland cement; the sand is river sand with a particle size of ≤5mm; the crushed stone particle size is 5mm~31.5mm; and the water reducer is a polycarboxylic acid type water reducer.
6. A process for preparing wet-mixed high-strength concrete according to claim 1, Features: The PVA fiber is pre-modified to obtain modified PVA fiber, which is then introduced into wet-mixed high-strength concrete; the specific modification process is as follows: PVA fiber is dispersed in a solvent, the pH is adjusted to 3-4, hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, N-hydroxyethyl-2-pyrrolidone, and glutaraldehyde are added, the temperature is raised to 55-60° C., stirred for 4-6 hours, washed, and dried to obtain modified PVA fiber.
7. A process for preparing wet-mixed high-strength concrete according to claim 6, Features: The modified PVA fiber comprises the following raw materials, calculated by weight: 10 to 15 parts of PVA fiber, 1 to 1.5 parts of hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, 0.5 to 1 part of N-hydroxyethyl-2-pyrrolidone, and 3 to 5 parts of glutaraldehyde.
8. A process for preparing wet-mix high-strength concrete according to claim 1, Features: The preparation of the hydroxylated basalt fiber comprises the following steps: Take basalt fiber, add it into Piranha solution, treat it at 90-95℃ for 1-2h, take it out, wash it and dry it to obtain hydroxylated basalt fiber.
9. A process for preparing wet-mixed high-strength concrete according to claim 8, Features: In the Piranha solution, V concentrated sulfuric acid: V hydrogen peroxide = (2-3): 1; the hydroxylated basalt fiber comprises the following raw materials, calculated by weight: 10-15 parts of basalt fiber and 60-80 parts of Piranha solution.
10. Concrete prepared according to the process for preparing wet-mix high-strength concrete according to any one of claims 1 to 9.
